Reactivity of mesoporous ZSM-5 zeolite towards friedel crafts acylation of anisole and propionic anhydride - Fatin Nur Syuhadah Mohd Jailani, 1994- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Kimia) - Universiti Teknologi Malaysia, 2017